1986
DOI: 10.1111/j.1526-4610.1986.hed2607356.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Muscle Contraction Headache Chronicity on Frontal EMG

Abstract: SYNOPSIS The purpose of this study was to test the effect of muscle contraction headache chronicity on electromyographic (EMG) response. Frontal EMG was measured under two stress conditions and three baselines for subjects complaining of muscle contraction headaches for (1) 3 19 years, (2) £ 10 years, and (3) subjects not complaining of headaches of any kind. There were ten subjects in each group. The three groups were equivalent in age and sex distribution. They did not differ in their ratings of the stressfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[2][3][4][5] There are several reasons for this controversy. Much of the earlier work focused on physiological responses to laboratory stressors 6,7 and not on the experience of naturally occurring stress. More recent studies have measured daily life stress over the past week or month and found that subjects diagnosed with TTH reported more stressful events at a greater magnitude than controls without headache.…”
mentioning
confidence: 99%
“…[2][3][4][5] There are several reasons for this controversy. Much of the earlier work focused on physiological responses to laboratory stressors 6,7 and not on the experience of naturally occurring stress. More recent studies have measured daily life stress over the past week or month and found that subjects diagnosed with TTH reported more stressful events at a greater magnitude than controls without headache.…”
mentioning
confidence: 99%
“…1 It is frequently characterized by the presence of electromyographic changes and/or "tender points" in the pericranium and the neck muscles. 2 Chronic migraine is characterized by an increasing frequency of migraine attacks until the headache becomes daily, albeit varying in intensity. 3 In fact, violent migraine attacks are often superimposed on a basis of chronic headache.…”
mentioning
confidence: 99%
“…Two studies that have examined sex differences among individuals with headache have found that in response to stress the reactions of men and women differ physiologically from one another. 5,14 Although no evidence was presented directly in support of perceptual or appraisal differences, the existence of sex differences in stress appraisal remains a possibility. We did not identify a large enough sample of men with headache to include in the present study and compare for gender effects.…”
Section: Prediction 1: Replication Of Previous Findings-mentioning
confidence: 99%
“…Given that those with headache differ from headache‐free participants in their appraisals of everyday stressors (ie, rating them as more stressful than do headache‐free participants), one might expect headache participants to rate laboratory stressors as more stressful than do controls. However, patients with tension‐type headache and controls do not differ in their subjective ratings of stress in the laboratory when ratings are made during or immediately following laboratory stressors 12,14,15 . Headache participants may report higher levels of stress before stressful laboratory tasks than do the controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation